Combination of LowDose Epigenetic Modifiers and TIC10 for the Activation of Antitumor Immunity and Inhibition of Tumor Growth in Gastrointestinal Cancer - Jianling Zou; Wentao Yang; Shuang Li; Fei Liu; Jinjia Chang; Wenhua Li; Mingzhu Huang; Xiaodong Zhu; Jianyin Zou; Weijian Guo; Zhiyu Chen (Cancer Medicine, 2025)
ABSTRACT Background Cytotoxic agents remain the mainstay treatment for advanced gastrointestinal cancer. However, the number of cytotoxic agents is limited, and the treatment effect is not satisfactory. Therefore, new agent and combination strategies are to be explored. Methods The antitumor efficacy of low‐dose epigenetic modifiers (LD‐EMs) of 5‐azacytidine and entinostat, cytotoxic agents of paclitaxel, cisplatin, oxaliplatin, 5‐fluorouracil, and a novel cytotoxic agent TIC10, and the combination of LD‐EMs and cytotoxic agents was investigated in vivo. Flow cytometry and immunohistochemistry were conducted to analyze the immune phenotype in the tumor microenvironment. The proliferation and apoptosis analyses were performed in vitro. Results LD‐EM therapy demonstrated superior tumor inhibition compared with commonly used chemotherapy in gastrointestinal cancer. A novel cytotoxic agent TIC10 resulted in weak to moderate tumor growth inhibition (TGI). LD‐EMs exhibited a more pronounced antitumor effect than TIC10 alone (CT26: TGI of 74.5% vs. 46.2%, respectively; p < 0.05; HNM007: TGI of 52.0% vs. 21.4%, respectively; p < 0.05; AKR: TGI of 53.8% vs. 10.1%, respectively; p < 0.05). The combination of TIC10 and LD‐EMs led to a more pronounced tumor reduction with tolerable toxicity. Analysis of the immune profiles showed increased percentages of CD45+ lymphocytes, CD3+ and CD8+ T cells, M1 macrophages, and dendritic cells, whereas decreased percentages of M2 macrophages and myeloid‐derived suppressor cells under treatment with LD‐EMs and combination therapy. Mechanistic studies revealed that LD‐EMs activated the RIG‐I–MAVS pathway, stimulated type I interferon responses, and subsequently promoted chemokine secretion. In contrast, TIC10 suppressed cell viability and induced cell apoptosis. Conclusions LD‐EMs remodeled the tumor microenvironment to an immune‐promoting environment. Although TIC10 could suppress cell viability and induce cell apoptosis. A combination of LD‐EMs and TIC10 indicated a rational strategy through complementary mechanisms.